Blood loss in obstetrics: the main stages of assistance - A V Kulikov; E M Schifman; S R Belomestnov; A V Zhilin; A A Matkovskiy; A S Bykov; S G Ababkov (IP Berlin A.V., 2015)
The article highlights the main stages of care for massive blood loss in obstetrics: the organization, risk assessment, prevention, damage control principle, the principle of control resuscitation, control of hemostasis and reaching the goal of treatment. The material is based on the latest achievements in the treatment of massive blood loss in obstetrics and real five-year practice of the Regional Perinatal Center in Yekaterinburg. Implementation phases of care for obstetric hemorrhage will allow to reduce the adverse consequences of this complication and to ensure organ-tactics.